PENGARUH LAMANYA PERENDAMAN UMBI DENGAN MOL TERHADAP VIABILITAS DAN VIGOR TANAMAN BAWANG MERAH Allium ascalonicum L.) - STEFANY DARSAN; Fany Juliarti Panjaitan; Yosni Kiuk; Elesta Banamtuan; Febby Suzanna Duka; Mariano Trivandy Ngasu Nganggo (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
This study aims to determine the effect of soaking duration of shallot bulbs using Local Microorganisms (MOL) on seed viability and vigor during the early growth phase. The research was conducted at the Agrotechnology Laboratory, Unit Stiper Petra Baliem Wamena, from April to August 2018 using a Completely Randomized Block Design (CRBD) with six MOL soaking duration treatments: 0 minutes (control), 30 minutes, 60 minutes, 90 minutes, 120 minutes, and 150 minutes, each repeated four times. The observed parameters included germination percentage, maximum growth potential, growth rate, plant height, and number of leaves at 14 days after planting (DAP). The results showed that MOL soaking treatments influenced the viability and vigor of shallot seeds. The highest germination percentage was obtained at the 60-minute treatment (95%), while maximum growth potential was relatively uniform across almost all treatments (100%). The highest growth rate was observed at the 150-minute soaking duration (85.57%), whereas the control treatment produced the lowest value (57.23%). Early vegetative growth also showed the best response at the 60-minute treatment, with plant height reaching 7.50 cm and the number of leaves reaching 10.75 at 14 DAPS.